Manipulation of Breath Alcohol Tests: Can Specific Techniques Alter Breath Alcohol Content? - Kelly, Brian (J Emerg Trauma Shock, 2020)
OBJECTIVE: The most common form of measurement of breath alcohol content (BrAC) is through the use of a diode catheter. This study aims to test the accuracy of breath alcohol analysis through different manipulations. METHODS: BrAC was measured after individuals consumed each standardized beer until they reached a 0.1 BrAC. Then, the individuals were breath analyzed while not providing full effort, using the side of their mouths, immediately after hyperventilating, 5 and 10 min after hyperventilation, immediately after a sip of water, and 5 min after that water. RESULTS: There were 54 individuals. Two baselines were used as the controls. The first baseline was a mean BrAC of. 104 with standard deviation of +0.008 for poor effort, side of mouth, and hyperventilating. The second baseline used for drinking water manipulations was a BrAC of 0.099 + 0.11. Poor effort (mean + standard deviation: 0.099 ± 0.10, P < 0.0001), immediately after hyperventilating (0.086 ± 0.011, P < 0.0001), 5 min after hyperventilating (0.099 ± 0.009, P < 0.0001), and 10 min after hyperventilating (0.099 ± 0.011, P < 0.0001) were all found to be statistically significant in their ability to lower BrAC. Both immediately after water (0.084 ± 0.011, P < 0001) and 5 min after drinking water (0.096 ± 0.13, P < 0.0001) were found to have significantly altered the BrAC. CONCLUSION: Our research shows that manipulations can alter BrAC readings significantly. Breath analyzer operators should be cognizant of these methods that may lead to falsely lower BrAC readings.